New-Onset Ulcerative Colitis in a Young Caucasian Woman with Unclassified Arteritis. (7th January 2022) - Roberts, Bryan
Abstract : Takayasu arteritis is a rare disease mostly found in Asian populations. Cases have been reported in patients with inflammatory bowel disease, suggesting possible genetic linkage. The objective of this clinical case report is to highlight a rare finding of arteritis signs and symptoms in a 32-year-old Caucasian woman (likely early that it did not yet meet classification for official diagnosis as Takayasu arteritis) who subsequently was diagnosed with ulcerative colitis a few months later. The patient presented to the hospital with throbbing neck pain and tenderness around the area of her right carotid artery distribution, nonspecific visual changes, and bilateral upper extremity paresthesia, with significant findings of 50-69% right carotid artery stenosis on a recent outpatient carotid Doppler ultrasound. Based on additional laboratory, clinical, and advanced imaging findings at the hospital, a diagnosis of arteritis not yet classifiable as Takayasu arteritis was made, and the patient was treated with corticosteroids. Unfortunately, she developed bradycardia that was later attributed to the corticosteroid regimen and the medication was discontinued. By follow-up in the clinic, the patient's carotidynia improved, but now, she reported a three-month history of bloody stools. Colonoscopy and pathology findings were consistent with ulcerative colitis, and the patient was started on mesalamine. The association of inflammatory bowel disease and Takayasu arteritis should not be overlooked, as future treatment methods and early, continuous surveillance may be critical in improving quality of life and avoiding serious complications.